Influence of Metal Precursors and Reduction Protocols on the Chloride‐Free Preparation of Catalysts for the Direct Synthesis of Hydrogen Peroxide without Selectivity Enhancers. Issue 8 (9th April 2016) - Sterchele, Stefano; Biasi, Pierdomenico; Centomo, Paolo; Shchukarev, Andrey; Kordás, Krisztián; Rautio, Anne‐Riikka; Mikkola, Jyri‐Pekka; Salmi, Tapio; Canton, Patrizia; Zecca, Marco
Abstract: Different metal precursors and reducing agents were applied in the preparation of 1 wt % Pd catalysts supported on commercial ion‐exchange resin (Lewatit K2621) and used in the direct synthesis of H2 O2 . The catalysts were characterized by using TEM and their performance was evaluated in the direct synthesis of H2 O2 (in a batch and semi‐batch reactor) to investigate the relationship between the catalyst preparation methods, morphology, and catalytic performance. As expected, both the choice of the Pd precursor and the reduction conditions had a strong influence on the size and size distribution of the resulting supported nanostructured metal nanoparticles and, consequently, on the catalytic performance. The best combination of metal precursor and reduction agent was [Pd(NH3 )4 ]SO4 reduced with hydrogen. This catalyst had the largest average size of the Pd nanoparticles and the broadest size distribution. Abstract : The direct approach : Metal precursors and reducing agents are studied in the preparation of catalysts for H2 O2 direct synthesis to investigate the relationship between catalyst preparation methods, morphology, and catalytic performance.